2020
DOI: 10.21203/rs.3.rs-32416/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Escherichia albertii in urinary and gastrointestinal infections in Kermanshah, Iran

Abstract: Background Escherichia albertii (E. albertii) is a Gram-negative and facultative anaerobe bacterium. In recent years, the bacterium has been isolated from the feces of people with gastroenteritis as a pathogen that causes diarrhea. Due to insufficient information on the phenotypic and biochemical characteristics of E. albertii, it is difficult to distinguish it from other species of the Enterobacteriaceae family. This is especially prevalent in the pathotypes of Escherichia coli (E. coli). Moreover, in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the present study, by using mdh and lysP genes, seven isolates had been identified as E. albertii in 100 isolates from urinary tract infections. A previous study had reported identification of 5 isolates as E. albertii among 60 isolates from urinary tract infections [6]. Higher prevalence of E. albertii was reported in previous studies from patients with diarrhea by the use of these two genes among isolates recognized as E.coli by biochemical reactions and phenotypic methods.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, by using mdh and lysP genes, seven isolates had been identified as E. albertii in 100 isolates from urinary tract infections. A previous study had reported identification of 5 isolates as E. albertii among 60 isolates from urinary tract infections [6]. Higher prevalence of E. albertii was reported in previous studies from patients with diarrhea by the use of these two genes among isolates recognized as E.coli by biochemical reactions and phenotypic methods.…”
Section: Discussionmentioning
confidence: 87%